2015
DOI: 10.1002/hbm.22756
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural brain abnormalities in Huntington's disease: A two‐year follow‐up

Abstract: Alterations in cross-sectional diffusion profiles between manifest HD subjects and controls were evident, both in whole-brain and striatum. In the preHD stage, only AD alterations were found, a finding suggesting that this metric is a sensitive marker for early change in HD prior to disease manifestation. The individual diffusivities were superior to FA in revealing pathologic microstructural brain alterations. Diffusion measures were well related to clinical functioning and disease stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 74 publications
(95 reference statements)
2
29
0
Order By: Relevance
“…We revealed that longitudinal increases in MD of the SFOF were prominent as individuals approached a motor diagnosis and correlated with disease burden. Past studies of prHD have not uncovered significant 18‐ to 24‐month longitudinal changes in WM using histogram analyses of the entire brain or skeleton‐based analyses of central WM fibers . Reasons for the discrepancies are unknown, but may relate to different analytic approaches and/or small prHD samples (ie, 22 to 28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We revealed that longitudinal increases in MD of the SFOF were prominent as individuals approached a motor diagnosis and correlated with disease burden. Past studies of prHD have not uncovered significant 18‐ to 24‐month longitudinal changes in WM using histogram analyses of the entire brain or skeleton‐based analyses of central WM fibers . Reasons for the discrepancies are unknown, but may relate to different analytic approaches and/or small prHD samples (ie, 22 to 28).…”
Section: Discussionmentioning
confidence: 99%
“…Although WM pathology correlates with disease burden in some studies, longitudinal studies are needed to chart the course of disease progression. However, most longitudinal dMRI studies of prHD have not found abnormal 12‐ to 30‐month changes in diffusivity profiles of whole‐brain WM, centers of WM tracts, or the striatum, although the latter result may relate to limitations of the tensor model in GM. Longitudinal dMRI findings contrast with 12‐ to 24‐month striatal, GM, and WM volume loss in prHD, suggesting that volumetric measures may be more sensitive to longitudinal changes.…”
mentioning
confidence: 98%
“…Diffusivity is an indirect marker of white matter tract organization. Increases of diffusivity across both the whole brain and in select white matter pathways, such as within the sensorimotor network, are suggestive of white matter degeneration in premanifest (preHD) and early manifest HD (Della Nave et al, 2010; Douaud et al, 2009; Dumas et al, 2012; Klöppel et al, 2008; Matsui et al, 2014; Novak et al, 2014; Odish et al, 2015; Poudel et al, 2014, 2015). In a recent study of the sensorimotor network, we observed a broad structural HD phenotype that encompassed gray and white matter volume, cortical thickness, and altered diffusivity in left white matter tracts in the sensorimotor network, which was associated with CAG repeat length (Orth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several longitudinal clinical studies have been performed. They showed a decrease in creatine and other metabolites (myo-inositol, N-acetylaspartate and choline) in striatum, white matter axial diffusivity and connectome changes in HD gene carriers during disease onset [44][45][46]. Various changes in brain metabolite concentration have also been found in different HD animal models (mice, non-human primates).…”
Section: Magnetic Resonance Imaging (Mri) and Spectroscopy (Mrs)mentioning
confidence: 90%